2017
DOI: 10.1016/j.celrep.2017.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Glutamate Co-transmission Does Not Affect Acquisition of Conditioned Behavior Reinforced by Dopamine Neuron Activation

Abstract: Summary Dopamine neurons in the ventral tegmental area (VTA) were previously found to express vesicular glutamate transporter 2 (VGLUT2) and to co-transmit glutamate in the ventral striatum (VStr). This capacity may play an important role in reinforcement learning. While it is known that activation of the VTA-VStr dopamine system readily reinforces behavior, little is known about the role of glutamate co-transmission in such reinforcement. By combining electrode recording and optogenetics, we found that stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 51 publications
7
32
0
Order By: Relevance
“…We then measured optogenetic-evoked excitatory postsynaptic currents (EPSCs) in striatal medium spiny neurons (MSNs) from these cKO mice. As previously reported (9,29,30), cKO mice lack glutamatemediated ChR2-evoked EPSCs, but following AAV-DIO-VGLUT2 expression, we observed 6,7-dinitroquinoxaline-2,3-dione-sensitive (DNQX-sensitive) EPSCs in all cKO MSNs assessed ( Figure 2C). This indicated that the heterologous expression of VGLUT2 is sufficient to endow glutamate release from midbrain DA neurons.…”
Section: Resultssupporting
confidence: 87%
“…We then measured optogenetic-evoked excitatory postsynaptic currents (EPSCs) in striatal medium spiny neurons (MSNs) from these cKO mice. As previously reported (9,29,30), cKO mice lack glutamatemediated ChR2-evoked EPSCs, but following AAV-DIO-VGLUT2 expression, we observed 6,7-dinitroquinoxaline-2,3-dione-sensitive (DNQX-sensitive) EPSCs in all cKO MSNs assessed ( Figure 2C). This indicated that the heterologous expression of VGLUT2 is sufficient to endow glutamate release from midbrain DA neurons.…”
Section: Resultssupporting
confidence: 87%
“…; Wang et al . ). In this study, we address the clinically important projection from the STN to the GP and introduce a validated method to perform and analyze enzyme‐based electrochemical recordings of glutamate upon optogenetic stimulation and to correct for artifacts.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study has provided first evidence for the possibility of measuring optogenetically evoked acetylcholine release (Gritton et al 2016) and we have recently reported the possibility to record glutamate release in the nucleus accumbens following optogenetic stimulation Wang et al 2017). In this study, we address the clinically important projection from the STN to the GP and introduce a validated method to perform and analyze enzyme-based electrochemical recordings of glutamate upon optogenetic stimulation and to correct for artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this result allows us to emphasize that our findings do not contradict the many other roles that dopamine has been shown to play when delivered for longer time periods or in situations less structured or constrained to isolate associative learning. Indeed, direct activation of dopamine neurons outside of a learning context clearly produces a motivation and behavioral drive that could be called value 7,[27][28][29][30][31][32] . In fact, it has recently been shown that directly pairing a cue with optogenetic activation of dopamine neurons, many times and without an obvious external precipitating event,…”
Section: Discussionmentioning
confidence: 99%